Reduce equaction to quadratic using substitution, Algebra

Solve 2 x10 - x5 - 4 = 0 .

Solution

We can reduce this to quadratic in form using the substitution,

u = x5

u 2  = x10

By using this substitution the equation becomes,

2u 2 - u - 4 = 0

It doesn't factor and thus we'll have to use the quadratic formula on it.  From the quadratic formula the solutions are,

U= (1 ±   √33 )/4

Now, to get back to x's we are going to require decimals values for these so,

u = (1 + √33 )/4 = 1.68614                       u = (1 -√33 )/4= -1.18614

Now, using the substitution to get back to x's gives the following,

u= 1.68614          x5  = 1.68614       x = (1.68614)(1/5)   = 1.11014

u =-1.18614       x5  = -1.18614        x =( -1.18614)(1/5)   = -1.03473

Certainly we had to employ a calculator to get the last answer for these. It is one of the cause that you don't tend to see too several of these done in Algebra class. The work and/or answers tend to be a little messy.

Posted Date: 4/6/2013 5:15:54 AM | Location : United States







Related Discussions:- Reduce equaction to quadratic using substitution, Assignment Help, Ask Question on Reduce equaction to quadratic using substitution, Get Answer, Expert's Help, Reduce equaction to quadratic using substitution Discussions

Write discussion on Reduce equaction to quadratic using substitution
Your posts are moderated
Related Questions
P=positive N=negative whats a negative - negative p+n= n-n=


is (1,7),(2,7),(3,7),(5,7) a function

Lee is taking some friends on a picnic. They''ll need to follow a path to get to the picnic spot. A map of the path is based on a scale of 1:30,000, in cm. If the path is 12 cm on


Any vector space V satisÖes the ten axioms, among which the last one is: "for any vector * u 2 V; 1 * u = * u; where 1 is the multiplicative identity of real numbers R:" Discuss th

Dependent system example Example: Solve the given system of equations. 2x + 5 y = -1 -10x - 25 y = 5 Solution In this instance it looks like elimination would b

Example   Evaluate following logarithms. log 4 16 Solution Now, the reality is that directly evaluating logarithms can be a very complicated process, even for those who

can you explain -12x-133= 67 - 2x

Convert following into the form                                        f (x ) = a ( x - h ) 2  + k Solution We are going to complete the square here.  Though, it is a s